Digital Literacy in Higher Education: A Bibliometric Analysis Using R-Biblioshiny - Iyoh Maspiroh; Nur Rohamtillah; Fani Yunida Anggraheni (Journal of Education Research, 2026)
This study aims to map trends and patterns in the literature related to digital literacy in higher education using a bibliometric approach. The research method involved bibliometric analysis based on data obtained from the Scopus database. The collected data consisted of publications from 2018 to 2024, with a total of 457 articles analyzed. Data analysis techniques employed OpenRefine for data validation, R-Biblioshiny for in-depth bibliometric analysis, and VOSviewer for network visualization. After validation through OpenRefine, the data were processed using R-Biblioshiny and visualized using VOSviewer. The findings indicate a significant increase in publications related to the integration of digital tools and online learning platforms in higher education. The results reveal that the bibliometric approach is capable of identifying dominant topics, collaboration patterns among authors, and future research opportunities. This study contributes by providing a comprehensive perspective for developing more effective and relevant digital literacy strategies in higher education.